Huanglong Antitussive Granule Relieves Acute Asthma Through Regulating Pulmonary Lipid Homeostasis - Yan, Hua; Qian, Guiying; Yang, Rui; Luo, Zichen; Wang, Xianzheng; Xie, Tong; Zhao, Xia; Shan, Jinjun (Frontiers in Pharmacology, 2021)
Background: Asthma is a respiratory disease with chronic airway inflammatory, and individuals with asthma exacerbations is one of the most frequent causes of hospitalization. Huanglong antitussive granule (HL Granule), a Chinese proprietary herbal medicine, has been proved to be effective in the clinical treatment of pulmonary disease. This study is devoted to the pharmacodynamics of HL Granule in acute asthma and the possible mechanism from the perspective of lipidomics. Methods: Mice were divided into four groups, control group, acute asthma model group, HL Granule treatment and Montelukast sodium treatment group. Acute asthma was induced by ovalbumin (OVA). Histopathology, pulmonary function and Enzyme linked immunosorbent assay (ELISA) were used to validated model and effect of HL Granule. Lipids were detected by ultra-high-performance liquid chromatography coupled to hybrid Quadrupole-Exactive Orbitrap mass spectrometry (UHPLC-Q-Exactive Orbitrap MS) and identified by MS-DAIL and built-in Lipidblast database. Differentially expressed lipids recalled in HL Granule treatment group were extracted for Heatmap, enrichment analysis and correlation analysis. Results: HL Granule was effective in decreasing airway hyperresponsiveness (AHR), airway inflammatory and the levels of IL-4 and IL-5. A total of 304 and 167 lipids were identified in positive and negative ion mode, respectively. Among these, 104 and 73 lipids were reserved in HL Granule group (FDR < 0.05), including acylcarnitine (ACar), fatty acid (FA), lysophosphatidylcholine (LPC), phosphatidylcholine (PC), lysophosphatidylethanolamine (LPE), phosphatidylethanolamine (PE), phosphatidylglycerol (PG), phosphatidylinositol (PI), phosphatidylserine (PS), diglyceride (DG), triglyceride (TG), sphingomyelin (SM) and ceramide (Cer). Furthermore, 118 and 273 correlations among 47 and 96 lipids in the positive and negative were observed, with ether-linked phosphatidylethanolamine (PEe) and phosphatidylcholine (PCe) (FDR < 0.001, Spearman correlation coefficient r2 > 0.75). Conclusion: HL Granule might improve pulmonary lipid homeostasis and could be used as an alternative or supplementary therapy in clinical for the treatment of asthma.